Maintenance and differentiation of human ES cells on polyvinylidene fluoride scaffolds immobilized with a vitronectin-derived peptide - Park, Sang Eun; Yeon, Gyu-Bum; Goo, Hui-Gwan; Seo, Dong Sik; Dayem, Ahmed A.; Lee, Kyung Eun; Park, Hyun-Mee; Cho, Ssang-Goo; Kim, Dae-Sung (John Wiley & Sons Inc., 2021)
Polyvinylidene fluoride (PVDF) is biocompatible, easy to fabricate, and has piezoelectric properties; it has been used for many biomedical applications including stem cell engineering. However, long-term cultivation of human embryonic stem cells (hESCs) and their differentiation toward cardiac lineages on PVDF have not been investigated. Herein, PVDF nanoscaled membrane scaffolds were fabricated by electrospinning; a vitronectin-derived peptide-mussel adhesive protein fusion (VNm) was immobilized on the scaffolds. hESCs cultured on the VNm-coated PVDF scaffold (VNm-PVDF scaffold) were stably expanded for more than 10 passages while maintaining the expression of pluripotency markers and genomic integrity. Under cardiac differentiation conditions, hESCs on the VNm-PVDF scaffold generated more spontaneously beating colonies and showed the upregulation of cardiac-related genes, compared with those cultured on Matrigel and VNm alone. Thus, VNm-PVDF scaffolds may be suitable for the long-term culture of hESCs and their differentiation into cardiac cells, thus expanding their application in regenerative medicine.